2005
DOI: 10.1007/s00381-005-1223-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of transient cerebellar mutism after cerebellar astrocytoma or medulloblastoma tumor resection in childhood

Abstract: Survivors who had TCM showed more speech deficits than controls or survivors without TCM. The data suggest that speech deficits are chronic if not permanent sequelae of TCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 25 publications
3
33
0
1
Order By: Relevance
“…71,105 These children also seemed more dysfluent, speaking at a slower speech rate than children without CM. Huber et al 46 considered that motor speech deficits persist for a long period of time (> 5 years), and similar findings were made by other authors. 52,81,92 Lastly, Robertson et al 82 tried to analyze the neurological outcome of their patients, and they found that there is a significant relationship among the level of initial severity of the syndrome and the severity of ataxia and language dysfunction and global intellectual handicap after 1 year.…”
Section: Outcomesupporting
confidence: 71%
See 1 more Smart Citation
“…71,105 These children also seemed more dysfluent, speaking at a slower speech rate than children without CM. Huber et al 46 considered that motor speech deficits persist for a long period of time (> 5 years), and similar findings were made by other authors. 52,81,92 Lastly, Robertson et al 82 tried to analyze the neurological outcome of their patients, and they found that there is a significant relationship among the level of initial severity of the syndrome and the severity of ataxia and language dysfunction and global intellectual handicap after 1 year.…”
Section: Outcomesupporting
confidence: 71%
“…The incidence of CMS has been reported to range from 8% 46 to 39%, 9,15,40,52,55,62,82,108 although there are reviews reporting a lower rate of 1.6%. 17 In the largest prospective study so far of 450 children who underwent surgery for medulloblastomas, the incidence of CMS was found to be 24%.…”
Section: Incidencementioning
confidence: 99%
“…They have speech deficits such as dysfluency, ataxic dysarthria, and slow speech rate (Huber-Okrainec et al, 2002) similar to those seen after acquired lesions of the cerebellum (Ackermann & Hertrich, 2000;Brown et al, 1970;Darley et al, 1969aDarley et al, , 1969bHuber et al, 2006Huber et al, , 2007Riva & Giorgi, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…El primero en describirlo fue Rekate en 1985 2 ; principalmente como un déficit postoperatorio en cirugías de fosa posterior 3,4 , aunque también se ha descrito secundario a infecciones [5][6][7][8] , trauma 9,10 o eventos isquémicos [11][12][13] . Es una complicación relativamente común después de una cirugía de fosa posterior (se ha descrito una incidencia entre el 11 y el 29% de los casos) 4,14,15 aunque su verdadera incidencia es difícil de determinar debido a problemas en la terminología y una definición variable del síndrome 16 . En la literatura existe una considerable superposición entre los términos "síndrome de fosa posterior", "mutismo cerebeloso", "mutismo acinético" y "mutismo con disartria posterior".…”
Section: Introductionunclassified